2020
DOI: 10.3390/su12166310
|View full text |Cite
|
Sign up to set email alerts
|

What are the Factors affecting Tourist Behavior based on the Perception of Risk? Romanian and Serbian Tourists’ Perspective in the Aftermath of the recent Floods and Wildfires in Greece

Abstract: During the summer season 2018 and 2019, natural hazards (namely, floods and wildfires) have occurred at some of the most popular tourist destinations in Greece, endangering tourists' safety and vacation quality. These have influenced tourists' perception of Greece as a "potentially risky destination, “causing a decrease in the number of tourists willing to visit this country. However, the current study assumes that some tourists will show more courageous travel behavior in the aftermath of natural hazards, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 94 publications
(157 reference statements)
1
18
0
Order By: Relevance
“…This is a new finding, given that neuropsychological traits of personality have not (to our knowledge) been investigated in relation to intention to travel during the COVID-19 pandemic. Previous studies investigating the role of personality in travel, in relation to perceptions of risks regarding wildfires, found that novelty-seeking and sensation-seeking were not related to courageous behavior [ 50 ]. Given that fun-seeking may represent openness to new experiences, searching for new rewards in an impulsive manner and, notably, low constraint [ 68 ], it may be a stronger predictor of the intention to travel when the risk of COVID-19 is still present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a new finding, given that neuropsychological traits of personality have not (to our knowledge) been investigated in relation to intention to travel during the COVID-19 pandemic. Previous studies investigating the role of personality in travel, in relation to perceptions of risks regarding wildfires, found that novelty-seeking and sensation-seeking were not related to courageous behavior [ 50 ]. Given that fun-seeking may represent openness to new experiences, searching for new rewards in an impulsive manner and, notably, low constraint [ 68 ], it may be a stronger predictor of the intention to travel when the risk of COVID-19 is still present.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about how personality affects travel intention and preferences during health crises such as the COVID-19 pandemic. Previous studies have shown that individuals who display higher levels of consciousness and novelty-seeking show more cautious behavior in traveling conditions, while individuals with higher levels of openness show less cautious behavior as a response to risk [ 50 ]. Other studies found most relations between personality traits and reactions to COVID-19 to be of small magnitudes [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, preventive behavior (e.g., keeping social distance, personal hygiene, wearing a facemask) is found to be positively correlated with the perceived level of risk [73]. Further, people who perceive lower personal risk show higher intention to visit and revisit a destination [70,[79][80][81]. Hence, we address these issues in the following research question: do people who are more prone to risk and intend to use hospitality services shortly after restrictions on movement are lifted care less about physical/social distancing and other safety-related protective measures?…”
Section: Tourism Recovery After Crisis and Perceptions Of Travel Risksmentioning
confidence: 97%
“…Since respondents were asked about in-country travel only, we can say that the perceptions are quite similar to an extent. Th e social and economic characteristics of the respondents also play a pivotal role in determining their travel attitude (Kovačić et al 2020). In case of Nepal, family pressure, economic pressure, and job and education related pressure might have increased the fractions of respondents that wish to avoid the travel during the COVID-19 pandemic.…”
Section: Post Restriction Travel Intentionmentioning
confidence: 99%